قراءة تأويليّة في رواية: (العدد صفر) لـ: (أمبرتو إيكو) - كماش, سارة; مجناح, جمال (University of El-oued, 2021)
تهدف الدّراسة إلى تطبيق نظرية التّأويل عند: (أمبرتو إيكو) في قراءة روايته: (العدد صفر)، وذلك بتتبع مسارات التّعضيد النّصيّ؛ أي بيان إحداثيات التّوقع الّتي يقدمها القارئ النّموذجيّ وهو يعاضد مختلف الفراغات المبثوثة في النّص باعتباره آلة كسولة، كما نسعى من خلال ذلك إلى بيان درجة انفتاح نص الرّواية، ونوعيّة القارئ النّموذجيّ الّذي يتوجه إليه. حيث كانت قراءتنا للروايّة قراءة تأويليّة وفق أسس التّعضيد النّصي، كما توسلنا بآليتي: الوصف والتّحليل. وقد توصلنا في ختام الدّراسة إلى أنّ نص الرّواية ينتمي إلى النّمط المفتوح؛ لأنّ الإستراتيجيّة النّصيّة وإن كانت تبدو لقارئ بسيط واضحة، إلّا أنّها معتمة، قائمة على التّلميح، وتتطلب قارئا بموسوعة مشبعة بسيناريوهات تناصيّة. كما خلصنا إلى أنّ (إيكو) قد وفّق - إلى حد كبير- في تحقيق الانسجام بين رؤاه النّقديّة وإبداعه الرّوائيّ. This study aims at implementing Eco’s theory of semiotics in reading his novel Numero Zero, mainly by following the mechanism of textual analysis. The ideal reader follows the aforementioned mechanism in order to link diversified gaps in the text as a lazy instrument. This article also aims at demonstrating the degree of openness of the novel, and the type of the ideal reader to whom it addresses. Therefore, this work answers the following research questions: To what extent the text of the novel is open to the act of interpretation? In other words, does the text address simple or discreet ideal reader? In our study, we used two mechanisms of description and analysis .The results reveal that the text of this novel belongs to the open style since the textual strategy, even if it seems clear for simple readers, is in fact a hint-based dark strategy that requires a reader with a large background. The findings also evince that Eco has succeeded to a great extent in harmonizing his critical insights with his novelistic creativity.
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج04. ع.02. جامعة الوادي
Keywords: التّعضيد النّصي، القارئ النّموذجي، الإستراتيجيّة النّصيّة، التّأويل، القراءة; Textual analysis, textual strategy, ideal reader interpretive, reading